Data Analysis on Interactive Whiteboards through Sketch-based Interaction - Browne, Jeffrey; Lee, Bongshin; Carpendale, Sheelagh; Henry Riche, Nathalie; Sherwood, Timothy (ITS 2011, 2011)
When faced with the task of understanding complex data, it is common for people to work on whiteboards, where they can collaborate with others, brainstorm lists of important questions, and sketch simple visualizations. However, these sketched visualizations seldom contain real data. We address this gap by extending these sketched whiteboard visualizations with the actual data to be analyzed. Guided by an iterative design process, we developed a better understanding of the challenges involved in bringing sketchbased interaction to data analysis. In this work we contribute insights into the design challenges of sketch-based charting, and we present SketchVis, a system that leverages hand-drawn input for exploring data through simple chart.